2018
DOI: 10.1002/jmri.26241
|View full text |Cite
|
Sign up to set email alerts
|

10‐Min 3D Turbo Spin Echo MRI of the Knee in Children: Arthroscopy‐Validated Accuracy for the Diagnosis of Internal Derangement

Abstract: 1 Technical Efficacy: Stage 6 J. MAGN. RESON. IMAGING 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 41 publications
0
33
0
1
Order By: Relevance
“…Further, the impact of implementation was not only enabling same‐day MRI in our practice for enhanced patient access and convenience, but also to reduce charges by two‐thirds. A similar model may be possible for other exams based on one or two volumetric scans . We are evaluating the use of T 2 Sh for other musculoskeletal exams in our institution, including a 5‐minute reduced TR acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the impact of implementation was not only enabling same‐day MRI in our practice for enhanced patient access and convenience, but also to reduce charges by two‐thirds. A similar model may be possible for other exams based on one or two volumetric scans . We are evaluating the use of T 2 Sh for other musculoskeletal exams in our institution, including a 5‐minute reduced TR acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, true clinical adoption with replacement of conventional 2D imaging is seldom described, likely due to persistent blurring artifacts. In recent work, a fast pediatric knee exam consisting of two 5‐minute 3D FSE scans has demonstrated excellent sensitivity and specificity compared with arthroscopy . A double‐echo steady state (DESS) sequence was also proposed for 3D coverage in 5 minutes, simultaneously providing morphology and quantitative T 2 values with near‐isotropic resolution .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But let us first have a look at some of the recent studies. In this issue of JMRI, Fritz et al report their experience with a 10‐minute MRI scan of the knee in pediatric patients. In 60 children with an age range of 2–16 years, two 3D, isotropic fast spin echo (FSE) sequences were used and three radiologists reviewed all images using multiplanar reformations.…”
Section: Recent Studiesmentioning
confidence: 99%
“…3 Advancements in parallel imaging and SMS research have shown promising results to accelerate 2D FSE protocols for knee MRI; however, such methods still preclude oblique slice reformations due to the acquisition of slices with high section-thickness. 4,5 3D-FSE sequences are promising for fast imaging [6][7][8] ; however, the diagnostic potential of such sequences may be limited due to image blurring induced by long echo trains. 3D balanced steady-state free-precession (bSSFP) sequences have also been explored, but bSSFP produces only singular contrast, which may not be adequate for comprehensive musculoskeletal imaging, and fat suppression is not always robust.…”
mentioning
confidence: 99%